Potential for geologically active faults department of antioquia, colombia (2014)
A geostatistics module ( mg95 ) was determined based on geostatistical studies of global estimations of seismicity data reported by the National Seismological Network of Colombia [Red Sismológica Nacional de Colombia (RSNC)]. It enabled the level of activity of the cortical fault in the Department of Antioquia (DA), Colombia to be categorized. The 95 mg relates the estimated values with polygonal kriging and the corresponding error for each one of the municipalities of Antioquia, with a Student parameter at 95% confidence, dependant on the number of microseisms registered locally. The following categorization scale is proposed to determine the levels of active faults in each municipality: proved active faultmg95 ∈ [0-0.2] , probable active faultmg95∈[0.2- 0.3] , and possible active faultmg95 and gt; 0..